Culture Teaching in Moroccan EFL Secondary Schools - AKHARRAZ, Mohamed; TAMER , Youssef (International Journal of Language and Literary Studies, 2021)
To empower Moroccan students to join the rapidly growing globalized world, the Ministry of education, through multiple official documents, incessantly calls for culture incorporation in the teaching of foreign languages. While the existing research studies on culture in the Moroccan EFL context have considerably revolved around textbook analysis, no study known to the researcher, has explored the real classroom practices of culture teaching in Moroccan secondary schools. Hence, this study explores how culture is being treated by the teaching practitioners at Moroccan secondary EFL classrooms – second-year Baccalaureate level. The thematic analysis of the data collected from 76 EFL instructors at Souss Massa Academy, through online questionnaires and interviews, has shown that the research participants demonstrated a good understanding of the culture teaching. However, the findings exhibited that plenty of challenges have made the linguistic components continue to pre-empt the significant portion of time in the classroom teaching. Based on the reported hurdles, a set of recommendations for the EFL teachers, ELT supervisors, textbook and curriculum designers, and further research were highlighted.